Feasibility of Romiplostim Discontinuation in Adult Thrombopoietin-Receptor Agonist Responsive Patients with Primary Immune Thrombocytopenia: An Observational Retrospective Report in Real Life Clinical Practice - Carpenedo, Monica (Hematol Rep, 2015)
Thrombopoietin mimetics are new treatment options for patients with immune throm-bocytopenia (ITP). Because of their mechanism of action, long-term administration was envisioned in order to maintain effective thrombopoiesis. We report on 30 romiplostim treated patients: 13/27 responders (48%) achieved stable platelet counts on a mean romiplostim dose of 2.43 µg/kg and were able to stop romiplostim after a mean of 44.3 weeks (range 12-122) on therapy with sustained response maintained at a mean of 26 months (range 12-52). No bleeding events occurred during the observational period. No specific patient’s features nor pattern of early response seemed to predict for sustained response. However, patients achieving safe platelet counts at lower dosages are probably worth a try of therapy tapering and discontinuation. Our observations support feasibility of romiplostim safe suspension in a relevant proportion of ITP patients.